PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS DEEP LEARNING PADA MATERI BANGUN RUANG UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG DI SEKOLAH DASAR - Rahmawati Rizqiyani; Liyana Sunanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The development of digital technology demands innovative learning media that can support elementary school students' understanding of concepts and numeracy skills, especially in abstract geometric shapes. This study aims to examine the potential of developing deep learning-based animated video media in improving elementary school students' numeracy skills and geometric understanding. The research method used is a Research and Development (R&D)-based literature study by analyzing various relevant journals, books, and scientific articles. Analysis techniques include content analysis and comparative analysis to identify advantages, limitations, and opportunities for developing learning media. The results of the study indicate that animated video media is effective in increasing students' motivation and numeracy learning outcomes, but still has limitations in analyzing calculation errors in depth. The integration of deep learning technology allows the development of adaptive and diagnostic media through numeracy error analysis, three-dimensional spatial visualization, and personalized learning. Thus, deep learning-based animated video media has the potential to be a more effective, interactive, and sustainable solution for elementary school students in learning geometric shapes.